The protection of indigenous knowledge within the current intellectual property rights regime: a critical assessment focusing upon the Masakhane Pelargonium case - Msomi, Zuziwe Nokwanda (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2013)
The use of indigenous knowledge (IK) and indigenous bio-resources by pharmaceutical and herbal industries has led to concerns about the need to protect IK in order to prevent biopiracy and the misappropriation of indigenous knowledge and resources. While some commentators believe that intellectual property rights (IPR) law can effectively protect IK, others are more sceptical. In order to contribute to the growing debate on this issue, this study uses the relatively new and as yet largely critically unanalysed Masakhane Pelargonium case to address the question of whether or not IPR law can be used to effectively protect IK. It is argued here that discussion about the protection of IK is a matter that must be located within broader discussions about North-South relations and the continued struggle for economic and political freedom by indigenous people and their states. The Masakhane case suggests that IPR law in its current form cannot provide sufficient protection of IK on its own. Incompatibilities between IPR law and IK necessitate that certain factors, most important of which are land, organised representation, and what are referred as 'confidence and network resources', be present in order for IPR law to be used with any degree of success. The study also reveals various factors that undermine the possibility of using IPR law to protect IK. In particular, the study highlights the way in which local political tensions can undermine the ability of communities to effectively use IPR law to protect their knowledge. The thesis concludes with several recommendations that will enable indigenous communities and their states to benefit more substantially from the commercialisation of their bio-resources and associated IK.
Keywords: Intellectual property -- South Africa -- Case studies; Cultural property -- Protection -- Law and legislation -- South Africa; Indigenous peoples -- Legal status, laws, etc -- South Africa; Masakhane (South Africa) -- Trials, litigation, etc; Pelargoniums -- Therapeutic use; Traditional ecological knowledge -- Law and legislation -- South Africa; Pharmaceutical industry -- Law and legislation -- South Africa